Evaluation and Treatment of Pediatric Spinal Cord Injury: State of the Art. - Jaramillo Ortiz, Roger Josué; Arreaga Cordova , Jose Luis; Cunache Baquerizo , Rafael Arnaldo; Ocampo Zambrano , Patricia Isabel; Guanopatin Vargas , Delcy Andreina (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Pediatric spinal cord trauma, though uncommon, has lasting repercussions on children’s development. This article reviews the current medical literature, focusing on the assessment, treatment, and management of spinal cord trauma in this population. Methodologically, recent studies were reviewed using databases such as PubMed, Scopus, and Web of Science, selecting articles from 2018 to 2024. The results highlight the complexity of pediatric spinal cord trauma. Anatomically, children’s spines are more susceptible due to their greater flexibility and disproportionate head size. The incidence is increasing, although trauma accounts for only 2% to 5% of all spinal cord injuries. Cervical injuries are more common in younger children, while thoracolumbar injuries prevail in adolescents. Mechanisms of injury include acceleration/deceleration and rotational forces. Injury assessment requires specific imaging techniques and careful consideration of the differences in children’s biomechanics. Innovations such as stem cell therapies and exoskeletons show potential to improve recovery, although more research is needed in pediatrics. In conclusion, spinal cord injuries in children require a multidisciplinary and ethical approach to manage their short- and long-term effects. While there are promising advances in treatments, ongoing evaluation is essential to effectively implement these innovations. Comprehensive and adaptive management is crucial to optimize outcomes in pediatric care.